THE EFFECT OF HELICOBACTER PYLORI ON INTERLEUKIN-6 IN PATIENTS WITH ISCHEMIC HEART DISEASE - Shahrazad H. Muhi; Wisal S. Abd; Najah S. Abd (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Several studies have shown that the presence of Helicobacter pylori (H. pylori) may be a risk factor for Ischemic Heart Diseases (IHD). Therefore, it is needed to look into the relation between IHD and H. pylori infection. One hundred Iraqi patients with IHD and 60 healthy Iraqis as a control group participated in the current study. The ELISA assay was used for the measurement of the sera levels for anti- H. pylori IgG, IgM, and Interleukin-6 (IL-6). Also, H. pylori DNA in the human venous blood was investigated by the polymerase chain reaction (PCR) using 16S rDNA primers. Between IHD patients and the control group, H. pylori-IgG and IL-6 mean ± SD were (Patient =1.814±0.08, Control = 0.823±0.09, Patient = 49.73±6.60, Control = 0.21±0.02, respectively), and this results showed a highly significant variation (p < 0.05) in anti-H. pylori IgG and IL-6, while no significant variations (p > 0.05) were found in anti- H. pylori IgM. It was also found that PCR amplification of Helicobacter pylori DNA using 16S rDNA primers was positive in the venous blood of 81 (81%) IHD patients. The current study results proposed that there was a relation between H. pylori and Ischemic Heart Disease.